Frequency of HTLV-1 seroconversion between pregnancies in Nagasaki, Japan, 2011–2018 - Komatsu, Nahoko; Iwanaga, Masako; Hasegawa, Yuri; Miura, Shoko; Fuchi, Naoki; Moriuchi, Hiroyuki; Yanagihara, Katsunori; Miura, Kiyonori (Frontiers in Microbiology, 2022)
Background. Human T-cell leukemia virus type-1 (HTLV-1) is transmitted vertically from an infected mother to her child via breastfeeding during infancy or horizontally via sexual contact. However, little information is available on the HTLV-1 seroconversion rate in pregnant mothers and the impact of new HTLV-1 infection on mothers and babies during the perinatal period. Methods. From the database of a prefecture-wide antenatal adult T-cell leukemia prevention program in Nagasaki, Japan, we extracted data on 57,323 pregnant women who were screened for anti-HTLV-1 antibody during 2011–2018. Data on the 16,863 subjects whose HTLV-1 proviral load (PVL) was measured more than twice were included in our analyses. Results. In total, 133 (0.79%) pregnant women were HTLV-1-positive during their first pregnancy and nine (0.05%) seroconverted before or during subsequent pregnancies (between pregnancies). The median PVL (per 100 peripheral blood mononuclear cells) was significantly lower in the seroconverted mothers (0.10%) than in the initially seropositive mothers (0.15%). A repeated measures correlation analysis for the individual PVLs of the HTLV-1-positive pregnant women showed that PVL increased with parity number (rrm = 0.25) with no perinatal problems. Conclusions. The HTLV-1 seroconversion rate between pregnancies was 0.05%, and their HTLV-1 PVL increased annually but no perinatal problems were noted.